On the role of genetic polymorphisms in the sulfation of cholesterol by human cytosolic sulphotransferase SULT2B1b. (25th April 2018) - Alherz, Fatemah A; Abunnaja, Maryam S; El Daibani, Amal A; Bairam, Ahsan F; Rasool, Mohammed I; Kurogi, Katsuhisa; Sakakibara, Yoichi; Suiko, Masahito; Liu, Ming-Cheh
Abstract: Sulphated cholesterol, like its unsulphated counterpart, is known to be biologically active and serves a myriad of biochemical/physiological functions. Of the 13 human cytosolic sulphotransferases (SULTs), SULT2B1b has been reported as the main enzyme responsible for the sulphation of cholesterol. As such, SULT2B1b may play the role as a key regulator of cholesterol metabolism. Variations in the sulphating activity of SULT2B1b may affect the sulphation of cholesterol and, consequently, the related physiological events. This study was designed to evaluate the impact of the genetic polymorphisms on the sulphation of cholesterol by SULT2B1b. Ten recombinant SULT2B1b allozymes were generated, expressed, and purified. Purified SULT2B1b allozymes were shown to display differential cholesterol-sulphating activities, compared with the wild-type enzyme. Kinetic studies revealed further their distinct substrate affinity and catalytic efficiency toward cholesterol. These findings showed clearly the impact of genetic polymorphisms on the cholesterol-sulphating activity of SULT2B1b allozymes, which may underscore the differential metabolism of cholesterol in individuals with different SULT2B1b genotypes.